2020
DOI: 10.1101/2020.05.30.20117291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EasyCOV : LAMP based rapid detection of SARS-CoV-2 in saliva

Abstract: Covid-19 crisis showed us that rapid massive virus detection campaign is a key element in SARS-CoV-2 pandemic response. The classical RT-PCR laboratory platforms must be complemented with rapid and simplified technologies to enhance efficiency of large testing strategies. To this aim, we developed EasyCoV, a direct saliva RT-LAMP based SARS-CoV-2 virus detection assay that do not requires any RNA extraction step. It allows robust and rapid response under safe and easy conditions for healthcare workers and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 14 publications
1
58
0
1
Order By: Relevance
“…The results can be read by observing the color of the sample inside the test tube. A color change from orange to yellow indicates that the sample is positive and SARS-CoV-2 is present ( L’Helgouach et al 2020 ).…”
Section: Point-of-care Technology For Salivary Diagnosis Of Covid-19mentioning
confidence: 99%
“…The results can be read by observing the color of the sample inside the test tube. A color change from orange to yellow indicates that the sample is positive and SARS-CoV-2 is present ( L’Helgouach et al 2020 ).…”
Section: Point-of-care Technology For Salivary Diagnosis Of Covid-19mentioning
confidence: 99%
“…There are several studies that demonstrated satisfying sensitivity and specificity of RT-LAMP for SARS-CoV-2 detection but little is known about its performance of testing clinical samples directly without RNA extraction [ [11] , [12] , [13] , [14] ]. In this study we evaluated the newly introduced CE-labeled variplex™ SARS-CoV-2 LAMP assay and compared the clinical performance with commercial RT-PCR tests.…”
Section: Objectivesmentioning
confidence: 99%
“…For a rapid diagnosis of SARS-CoV-2 cost-effective methods with low hands-on time that circumvent limitations of RT-PCR may be helpful tools for a routine diagnostic workflow [ 9 , 11 ]. RT-loop-mediated isothermal amplification (LAMP) may offer the possibility to be established as an alternative diagnostic technique [ [12] , [13] , [14] ]. The combination of RT with Bst polymerase possessing a DNA strand displacement activity allows amplification of target genes at a constant temperature in less than one hour.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilizing saliva: Liberating RNA genomes from virions, protecting RNA from degradation, and dealing with pH variability in human saliva Multiple studies have developed methods for using saliva samples in combination with RT-LAMP specifically with a colorimetric readout (Lalli et al, 2020;L'Helgouach et al, 2020; Rabe and Cepko, 2020). However, the inherent variance in the acidity of saliva samples in a population, which can vary between 6.8 and 7.4 (Cameron et al, 2015), poses a significant problem because the colorimetric readout for RT-LAMP is pH-dependent.…”
Section: Figure 1: Optimized Rt-lamp Parameters For Detecting Sars-comentioning
confidence: 99%